Hoteliers' perception of corporate crisis and crisis management in the Singapore hotel industry. - Chen, Jian Hao. (2008)
This report looks at the perceptions of corporate crisis of four local hoteliers belonging to the 5-star, luxury hotel segment in the local industry, and their hotels’ crisis management plans. It was found, through surveys and interviews, that they perceive corporate crisis as disruptions to normal operations and/or damage to hotel assets. Hence, a definition for corporate crisis was proposed based on their overall perspectives. Judging from the hoteliers’ crisis plans and managing practices, their hotels were generally well prepared for corporate crises, and they do place great emphasis on crisis management.